The application of geographical information system (GIS) mapping the wind hazard in Perlis, Malaysia - Nuriasnizam , Mat Din (2012)
In past a few years records there are reported the wind hazard occurred across Malaysia due to strong wind storm that uplifting of roof structure and also others parts of structures in building. There are numbers of factors that contribute the wind hazard development such as the roughness of terrain and the topographical location. The factor such as terrain roughness can also contribute and cause of wind hazard. The topographic effect are also have considers in this study. The understanding of wind characteristic behaviour is not well defined. Mostly, the designers or engineers only considered the wind direction and wind speed in design structure. Therefore, the study is to produce the database of wind hazard map in Perlis state by using Geographical Information System (GIS). From this result, it shown that area that have highest numbers of wind hazard occurred and the effect of topographical factors and roughness of terrain contribute to the wind hazard. Form analysis had been done, wind damage frequently occurred around Kangar area where the terrain category is Category 4, where the terrain with numerous larges, high (10.0 m to 30.0 m high) and closely spaced obstruction such as large city centres and well-developed industrial complexes. It can be concluded the the topography and roughness of terrain will be significant factor that contribute to wind hazard.